2020
DOI: 10.31219/osf.io/n3chy
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pengaruh Penerapan Model Pembelajaran Poe2we Berbasis Hands on Activity Pada Materi Induksi Elektromagnetik Terhadap Kemampuan Berpikir Kritis Siswa

Abstract: Model pembelejaran POE2WE merupakan model pembelajaran yang dikembangkan untuk mengetahui pemahaman siswa mengenai suatu konsep dengan pendekatan konstruktivistik. Dengan kata lain, pembelajaran yang menggunakan konstruktiv siswa sebagai pusat pada pembelajaran. Hands On activity adalah suatu kegiatan yang dirancang untuk melibatkan siswa dalam mencari informasi dan bertanya, beraktivitas dan menemukan, mengumpulkan data dan menganalisis, serta membuat kesimpulan sendiri. Latar belakang masalah penelitian ini … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The scientific approach can improve argumentation skills because the 5M activities (observing, asking, trying, associating and communicating) facilitate students to connect data with claims that are formed and strengthened by justifications (warrants) and supports (backings) (Siswanto et al, 2014;Mubarok et al, 2016;Nasir & Suryani, 2018). Biology learning that is carried out with scientific investigations trains students to solve problems by doing scientific work so that students can consider evidence and data, draw conclusions, test and evaluate a theory (Duschl & Osborne, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The scientific approach can improve argumentation skills because the 5M activities (observing, asking, trying, associating and communicating) facilitate students to connect data with claims that are formed and strengthened by justifications (warrants) and supports (backings) (Siswanto et al, 2014;Mubarok et al, 2016;Nasir & Suryani, 2018). Biology learning that is carried out with scientific investigations trains students to solve problems by doing scientific work so that students can consider evidence and data, draw conclusions, test and evaluate a theory (Duschl & Osborne, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies on the use of scientific approaches in relation to the ability to argue have been carried out, concluded that scientific approaches have a strong influence on students' scientific argumentation ability [6]. Scientific methods can significantly improve students' argumentation skills [7].…”
Section: Introductionmentioning
confidence: 99%